Antiarrhythmic and α‐Adrenoceptor Antagonistic Properties of Novel Arylpiperazine Derivatives of Pyrrolidin‐2‐one. Issue 12 (2nd November 2015) - Zaręba, Paula; Dudek, Magdalena; Lustyk, Klaudia; Siwek, Agata; Starowicz, Gabriela; Bednarski, Marek; Nowiński, Leszek; Zygmunt, Małgorzata; Sapa, Jacek; Malawska, Barbara; Kulig, Katarzyna
Abstract : In an effort to develop α‐adrenoceptor antagonists with antiarrhythmic activity, we designed a series of pyrrolidin‐2‐one derivatives. The α1 ‐ and α2 ‐adrenorecepor affinities of the new pyrrolidin‐2‐one derivatives were determined using a radioligand binding assay. The most active compound was then tested in vitro for intrinsic activity toward α1A ‐ and α1B ‐adrenoceptors and in vitro for antiarrhythmic activity in epinephrine‐induced arrhythmia in rats. The highest affinity for the α1 ‐adrenoceptor (p K i = 7.01) was displayed by 1‐4‐[4‐(2‐methoxy‐5‐chlorophenyl)‐piperazin‐1‐yl]‐methyl‐pyrrolidin‐2‐one (9 ). 1‐[4‐(2‐Fluorophenyl)‐piperazin‐1‐yl]‐methyl‐pyrrolidin‐2‐one (7 ) showed the highest affinity toward the α2 ‐adrenoceptor (p K i = 6.52). Intrinsic activity studies of compound9 showed that this compound is an antagonist of both α1A ‐ (EC50 = 0.5 nM) and α1B ‐ (EC50 = 51.0 nM) adrenoceptors. Compound9 displayed antiarrhythmic activity in rats (ED50 = 5.0 mg/kg (3.13–7.99)). New derivatives of pyrrolidin‐2‐one with α1 ‐adrenoceptor affinity were identified. We propose that the antiarrhythmic activity of compound9 is related to its antagonism of α1A ‐ and α1B ‐adrenoceptors. Abstract : A series of new pyrrolidin‐2‐one derivatives (2 –12 ) were synthetized and assessed for their α‐adrenoceptor affinity. The most promising compound (9 ) was further tested for its antiarrhythmic activity, which turned out to be related to its antagonism at the α1A ‐ and α1B ‐adrenoceptors.